THE LEVEL OF AWARENESS, DIFERENTIATION, AND BRAND VALUE IN CONSTRUCTING FARMER PERCEPTION INFLUENCING THE DECISION OF CORN SEED HIBRIDA PURCHASE - Riyanti Isaskar; Rini Dwi Astuti; Peterson Silalahi (UNEJ e-Proceeding, 2012)
Looking at the competition in a market that is so tight, a consumer perception of a brand is very important, because manufacturers know that knowledge is used to marketingstrategy. The perception of a person can form due to lack of awareness, differentiation, andthe value provided by a brand. The purpose of the implementation of research i.e. knowingthe level of awareness, differentiation, and value brand in the construct perceptions offarmers in hybrid corn seeds, and analyzing the simultaneously and the partially influencevariables of brand awareness, differentiation, and value of brand that affect the decision ofthe purchase of hybrid corn by farmers. The results obtained the overall perception of thefarmers who formed on the basis of the level of awareness, differentiation, and value brandof the majority are on a negative category, due to the logistical regression model using theresult that there are simultaneously influence toward brand awareness, branddifferentiation, and value brand of hybrid corn seed purchase decisions. From the testpartial correlation revealed that the variable brand value most affecting of farmers 'decision in buying a hybrid corn seeds merk X.